Papers presented at the Eighteenth International Conference on Patristic Studies held in Oxford 2019. - Vinzent, Markus (Studia Patristica ;, 2021)
The successive sets of 'Studia Patristica' contain papers delivered at the International Conferences on Patristic Studies, which meet for a week once every four years in Oxford. These papers range over the whole field, both East and West, from the second century to a section on the 'Nachleben' of the Fathers. The majority are short papers dealing with some small and manageable point; they raise and sometimes resolve questions about the authenticity of documents, dates of events, and such like, and some unveil new texts. The longer papers put such matters into context and indicate wider trends. The whole reflects the state of Patristic scholarship and demonstrates the vigour and popularity of the subject.